Enhanced biomass and lipid production by light exposure with mixed culture of Rhodotorula glutinis and Chlorella vulgaris using acetate as sole carbon source. (November 2022) - Gong, Guiping; Wu, Bo; Liu, Linpei; Li, Jianting; He, Mingxiong; Hu, Guoquan
Graphical abstract: Highlights: Acetate was applied to produce microbial biomass and lipids by yeast/algae co-culture. Co-culture facilitates acetate utilization efficiency thus reducing culture period. Increasing algae proportion promoted biomass productivity and acetate assimilation. Light-exposed synergetic effect further increased cell growth and lipid titer. More neutral lipids and linolenic acid were accumulated with light-exposed co-culture. Abstract: Microbial biomass and lipid production with mixed-culture of Rhodotorula glutinis and Chlorella vulgaris using acetate as sole carbon source was investigated. Synergistic effect of mixed-culture using 20 g/L acetate significantly promoted cell growth and acetate utilization efficiency. Increasing the proportion of algae in co-culture was beneficial for biomass and lipid accumulation and the optimal ratio of yeast/algae was 1:2. Light exposure further enhanced biomass and lipid titer with 6.9 g/L biomass and 2.6 g/L lipid (38.3 % lipid content) obtained in a 5L bioreactor. The results of lipid classes and fatty acid profiles moreover indicated that more neutral lipids and linolenic acid were synthesized in mixed-culture under light exposure condition, suggesting the great potential in applications of biofuels production. This study provided new insight and strategy for economical microbial biomass and lipid production by light-exposed mixed-culture using inexpensive acetate as carbon source.